Evaluation of Leptospira interrogans knockdown mutants for LipL32, LipL41, LipL21, and OmpL1 proteins - Fernandes, Luis G. V.; Teixeira, Aline F.; Nascimento, Ana L. T. O. (Frontiers in Microbiology, 2023)
Leptospirosis is a worldwide zoonosis caused by pathogenic and virulent species of the genus Leptospira, whose pathophysiology and virulence factors remain widely unexplored. Recently, the application of CRISPR interference (CRISPRi) has allowed the specific and rapid gene silencing of major leptospiral proteins, favoring the elucidation of their role in bacterial basic biology, host-pathogen interaction and virulence. Episomally expressed dead Cas9 from the Streptococcus pyogenes CRISPR/Cas system (dCas9) and single-guide RNA recognize and block transcription of the target gene by base pairing, dictated by the sequence contained in the 5´ 20-nt sequence of the sgRNA. In this work, we tailored plasmids for silencing the major proteins of L. interrogans serovar Copenhageni strain Fiocruz L1-130, namely LipL32, LipL41, LipL21 and OmpL1. Double- and triple-gene silencing by in tandem sgRNA cassettes were also achieved, despite plasmid instability. OmpL1 silencing resulted in a lethal phenotype, in both L. interrogans and saprophyte L. biflexa, suggesting its essential role in leptospiral biology. Mutants were confirmed and evaluated regarding interaction with host molecules, including extracellular matrix (ECM) and plasma components, and despite the dominant abundance of the studied proteins in the leptospiral membrane, protein silencing mostly resulted in unaltered interactions, either because they intrinsically display low affinity to the molecules assayed or by a compensation mechanism, where other proteins could be upregulated to fill the niche left by protein silencing, a feature previously described for the LipL32 mutant. Evaluation of the mutants in the hamster model confirms the augmented virulence of the LipL32 mutant, as hinted previously. The essential role of LipL21 in acute disease was demonstrated, since the LipL21 knockdown mutants were avirulent in the animal model, and even though mutants could still colonize the kidneys, they were found in markedly lower numbers in the animals´ liver. Taking advantage of higher bacterial burden in LipL32 mutant-infected organs, protein silencing was demonstrated in vivo directly in leptospires present in organ homogenates. CRISPRi is now a well-established, attractive genetic tool that can be applied for exploring leptospiral virulence factors, leading to the rational for designing more effective subunit or even chimeric recombinant vaccines.